Assessing the quality of operation notes: a review of 1092 operation notes in 9 UK hospitals. Issue 1 (December 2016) - Unknown
Abstract Background The General Medical Council states that effective note keeping is essential and records should be clear, accurate and legible. However previous studies of operation notes have shown they can be variable in quality and affect patient safety. This study compares the quality of operation notes against the National Standards set by the Royal College of Surgeons of England and the British Orthopaedic Association (BOA) for improving patient safety. Methods Information from Orthopaedic operation notes was collected prospectively over a 2-week period. All elective and trauma operations performed were included and trainees from the region coordinated data collection in 9 hospitals. Results Data from 1092 operation notes was reviewed. A number of important standards were nearly met including legibility (98.4 %), the name of the operating surgeon (99.3 %) and the operation title (99.1 %). However a number of standards were not met and those with potential patient safety implications include availability on the ward (88.8 %), documentation of type of anaesthetic used (78.6 %), diagnosis (73.4 %) and findings (80.1 %). In addition, the postoperative instructions recorded the need for and type of postoperative antibiotics or venous thromboembolism prophylaxis in only 49.7 % and 48.8 % of cases respectively. Conclusions The quality and content of operation notes studied across the region in this period was variable. Use of software programmes in some hospitals for creating operation notes meant that some centres had better results for elements such as date, time and patient identification details. Following this study, greater awareness of the standards combined with additional local measures may improve the quality of operation notes.